Is cork oak (Quercus suber L.) woodland loss driven by eucalyptus plantation? A case-study in southwestern Portugal - Costa, a; Madeira, M.; Santos Lima, J.; Costa A, Madeira M.; J, Santos Lima (iForest - Biogeosciences and Forestry, 2014)
Mediterranean landscapes with open cork oak (Quercus suber L.) woodlands have recently experienced drastic changes in southwestern Portugal. Changes in agricultural activities, the traditional driver of the economy in this region, led to new land uses such as long-term set aside (shrublands) and eucalyptus plantations. A study was conducted on the oak woodland landscape dynamics over a 50-year period (from 1958 to 2007) in order to assess the effect of different biophysical conditions on landscape spatial changes, and to identify the resilience of lanscape composition to different disturbances (e.g., socio-economic changes and wildfires). Land use changes over two consecutive periods (1958-1995 and 1995-2007) were inferred by spatial analysis of land cover data (aerial photographs) and related to landscape physical attributes (slope and soil type). A transition matrix of four vegetation land-cover classes was obtained, allowing the assessment of the landscape composition changes bewteen the two above periods. Results showed that lansdcape in 1958 was largely occupied by open farmland, with large patches of open oak woodlands on steep slopes surrounding watercourses. Open farmland and shrubland drastically declined from 1958 to 1995, while eucalyptus plantation exhibited a dramatic expansion. Although large areas of cork oak forest turned into eucalyptus plantation, the net loss of oak forest was low and counterbalanced by its increment on former open farmland. The occurrence of a wildfire in 2003 promoted a dramatic decrease in cork oak woodlands, which mostly turned into shrubland. However, shrubland may be considered “safe sites” for ecological succession, ensuring natural cork oak regeneration and the colonization of neighboring areas.
Keywords: agroforestry systems; Eucalyptus Plantations; evergreen oak woodlands; Land Cover; Mediterranean Climate Region; Quercus suber L.

Cork oak woodlands patchiness: A signature of imminent deforestation? - Costa, Augusta; Madeira, Manuel; Plieninger, Tobias (Applied Geography, 2014)
The cork oak (Quercus suber L.) woodlands of the agroforestry landscapes of Southwestern Iberia are undergoing drastic change due to severe natural and anthropogenic disturbances. These may eventually result in woodland loss or deforestation, the final step of an ongoing process of woodland degradation. Monitoring changes in the spatial patterns of woodlands – especially fractional canopy cover of woodlands and/or their patchiness in the landscape mosaic – potentially enables forecasting of loss and responding to it at an early stage. We examine the degradation process in two cork oak woodlands, resulting from distinct disturbances, wildfire and oak mortality, aimed at evaluating the changes, trends and deviations of the spatial attributes of these woodlands as they move from an initial (less disturbed ecosystem) to a final state (more disturbed ecosystem). While undergoing disturbances, both woodlands exhibited similar trends of decreasing fractional canopy cover and decreasing number of larger patches. Patchiness rather than fractional canopy cover seems, however, to be potentially more useful as a signature of imminent oak woodlands deforestation, given that its contrast before and after disturbance was much higher. The structural dynamics of oak woodlands is a crucial but neglected issue that needs greater attention from policy forums working toward their conservation and restoration as well as from stakeholders and society as a whole.
Keywords: Forest degradation; Fractional canopy cover; mediterranean landscape; Patch size–frequency distribution; Power-law function; Quercus suber L.

Decline of Mediterranean oak trees and its association with Phytophthora cinnamomi: a review - de Sampaio e Paiva Camilo-Alves, Constança; Clara, MariaIvoneEsteves; Almeida Ribeiro, NunoManuelCabral (European Journal of Forest Research, 2013)
Mortality events in cork and holm oaks have occurred in the Mediterranean basin since the beginning of the XX century, but severity of decline increased during the 1980s. By that time, the exotic soil borne pathogen Phytophthora cinnamomi was often recovered from declining stands and since then it has been considered the main factor associated with decline. This work analyses data concerning P. cinnamomi surveys in cork and holm oaks trees, pathogenicity tests carried out in controlled experiments, studies about the influence of site characteristics in tree decline and approaches to control the disease. Results of field surveys showed that the pathogen is widespread and pathogenicity tests suggested that host susceptibility to the pathogen is moderate when seedlings are in appropriate watering conditions, particularly cork oaks. Occurrence of decline is also associated with soil characteristics that interfere with root expansion and water retention. We assessed the relative importance of each factor involved in decline and revised the role of P. cinnamomi in cork and holm oak decline.
APSAPSThe following values have no corresponding Zotero field: publisher: Springer-Verlag
Keywords: mortality; pathogenes; Quercus ilex L.; Quercus suber L.; tree decline

Establecimiento de cultivos en suspensión para la producción en masa de embriones somáticos en alcornoque y pino piñonero - CELESTINO MUR, C.; RUIZ-GALEA, M.; ALONSO BLÁZQUEZ, N.; BARRA JIMÉNEZ, A.; ALEGRE ÁLVARO, J.; TORIBIO IGLESIAS, M. (VI Congreso Forestal Español, 2013)
La clonación mediante embriogénesis somática es hoy una biotecnología bien establecida en la industria forestal, posibilitando la regeneración de plantas a partir de individuos selectos y el establecimiento de plantaciones multivarietales de alto valor productivo. El potencial de esta biotecnología se ve condicionado por la recalcitrancia que muestran algunas especies, genotipos o explantos para responder a las condiciones de cultivo impuestas. La producción a gran escala de embriones somáticos requiere el establecimiento de cultivos en suspensión, los cuales proporcionan mayores tasas de producción y sincronización de los embriones somáticos que las obtenidas en medio semisólido, prerrequisito para la automatización de esta biotecnología. Hemos obtenido la regeneración de plantas por embriogénesis somática en medios semisólidos, usando brotes de hojas de alcornoque y a partir de semillas inmaduras en pino piñonero. También hemos establecido cultivos en suspensión en ambas especies. Se describe, entre otros factores, el efecto de la densidad de inoculación, el volumen del envase y la velocidad de agitación, en la proliferación de líneas embriogénicas y diferenciación de embriones somáticos para ambas especies. El tamaño y la densidad del inóculo determinaron fuertemente el crecimiento de los cultivos. La velocidad de agitación y las características del envase influyeron sobre todo en la organización de las estructuras embriogénicas.
The following values have no corresponding Zotero field: periodical: VI Congreso Forestal Español pub-location: Vitoria
Keywords: Biotecnología forestal; embriogénesis somática; Pinus pinea L.; Quercus suber L.

Textural and Surface Characterization of Cork-Based Sorbents for the Removal of Oil from Water - Pintor, Ariana M. A.; Silvestre-albero, Ana M.; Ferreira, Catarina I. A.; Pereira, Joana P. C.; Vilar, V. J. P.; Botelho, M. S.; Rodr, Francisco; Boaventura, Rui A. R. (Industrial & engineering chemistry research, 2013)
This study evaluates the possibility of adding value to cork granulates, byproducts of cork processing, by using them as biosorbents and precursors of activated carbons. Activation was carried out by impregnation with phosphoric acid followed by pyrolysis under N2 flow. Furthermore, biosorbents were treated with a cationic surfactant and activated carbons were subject to a second pyrolysis under propene with the objective of improving hydrophobicity. Physico-chemical, textural, and surface characterization of the materials was carried out employing, among others, N2 adsorption isotherms, Fourier transform infrared (FTIR) spectroscopy, potentiometric titration, temperature programmed desorption (TPD), and immersion calorimetry. Selected samples were tested in the removal of sunflower oil emulsified in water. Activated carbons with higher surface area and lower amount of acidic surface groups showed higher uptake capacity for sunflower oil
APSAPS
Keywords: biosorbents; cork products; Quercus suber L.; sunflower oil

Analysis of phenolic compounds in cork from Quercus suber L. by HPLC–DAD/ESI–MS - Fernandes, Ana; Sousa, André; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Food Chemistry, 2011)
The aim of the present work was to identify the extractable phenolic compounds present in cork from Quercus suber L. The structures of thirty three compounds were tentatively identiﬁed by liquid chromatography coupled to electrospray ionisation mass spectrometry (HPLC–DAD/ESI–MS). The majority of those compounds were gallic acid derivatives, in the form of either galloyl esters of glucose (gallotannins), combinations of galloyl and hexahydroxydiphenoyl esters of glucose (ellagitannins), dehydrated tergallic-C-glucosides or ellagic acid derivatives. Others were found to correspond to low molecular weight phenolic compounds, like acids and aldehydes. Mongolicain, a ﬂavanoellagitannin in which hydrolysable tannin and ﬂavan-3-ol moieties are connected through a carbon–carbon linkage, was also detected in cork from Q. suber L. The results illustrate the rich array of phenolic compounds present in cork.
Keywords: Cork; ellagitannins; Flavanoellagitannins; LC-DAD/ESI-MS; phenolic compounds; Quercus suber L.

Déprédation des glands de chêne liège par les insectes et possibilités de germination et de croissance des semis - BOUCHAOUR-DJABEUR, Sabéha; BENABDELI, Khéloufi; Bejamaa, Mohamed Lahbib; Stiti, Boutheina (Geo-Eco-Trop, 2011)
Depredation of the acorns cork oak by the insects and its impact on the potential of germination and seedling growth were studied in a mountain cork oak forest in northwestern Algerian. The rate of pre-germinated acorns on the ground is higher than for other acorns. The weight is the most distinctive variable for all the acorns; whatever their condition and provenance, it varies significantly from 0.76 to 6.76 g. Regarding the damage to acorns, statistical tests show no significant difference in the length and weight, it is not very significant for the width.The infestation of acorns is independent of their size. The acorns attacked by beetles are clearly dominant (72%) compared with those attacked by moths (28%). 20% severely damaged acorns germinate and produce viable seedlings. But the germination rate decreases with the increase of injuries. Growth is strongly affected by the rate of damage to acorns. One therefore concludes that a major attack in the cotyledons certainly does not act on germination, but can affect the strength of the resulting plant and its survival.
Keywords: aspects of the acorns; Growth; infest by the insects; period of harvest; Quercus suber L.; resistance

Fungal fruitbodies and soil macrofauna as indicators of land use practices on soil biodiversity in Montado - Azul, Anabela Marisa; Mendes, Sara Margarida; Sousa, José Paulo; Freitas, Helena (Agroforestry Systems, 2011)
The impacts of land use on soil biodiversity are still poorly understood, although soil fungi and macrofauna are recognized to provide beneÞts to ecosystems. Here, we tested whether land use practices used to control shrub density inßuences the fruiting macromycetes (ectomycorrhizal-forming fungiÑ ECMFÑand saprobes) and soil macrofauna diversity and abundance in Montado ecosystems. To address this inßuence, we conducted a 2-yearsÕ period monitoring of fungi fruitbodies and macrofauna in sixteen experimental plots in Montado landscape in southern Portugal. A total of 4,881 frutibodies (57 taxa of ECMF and 64 taxa of saprobic fungi) and 3,667 soil invertebrates (73 species and morphospecies) were monitored in the experimental plots. There was greater losses in sporocarps production and taxa composition, particularly the ECMF, in plots where shrub density was controlled by permanent grazing (Ca) or involving cutting practices followed by soil tillage (M), in comparison with cutting practices with no soil tillage (Cu) and the control (C). The ECMFLaccaria laccata and Xerocomus subtomentosus exhibited a close relation with C and Cu plots while the saprobes, e.g., Entoloma conferendum, were associated to Ca and M plots. Most species associated to Cu plots were present in C plots during the 2 years, but not in Cu after the cutting practices (in the second year of sampling). Regarding soil macrofauna, higher values of taxa and species richness were observed in C and Cu plots in the Þrst year of sampling. The ant species Aphaenogaster senilis and several Staphylinid morphospecies exhibited a close relation with M plots, whilst most spider families were directly associated to C and Cu plots. After the shrub cutting practices, higher values of taxa and species richness of soil macrofauna were observed in M and Ca plots; the presence of species with a high competitive ability to colonize disturbed areas faster might explain the results. Contrary to the frutibodies production and diversity, species richness and abundance within soil macrofauna were identical between Cu and C in 2004. Thus, fruiting macromycetes and soil macrofauna diversity and abundance in MontadoÕs, appear highly sensitive to land use and somewhat reßected a trend of severity to the current shrub management practices.
Keywords: Ecosystems monitoring; Fungal fruit-body; fungal fruit-body á soil; land use; macrofauna á; montado; Quercus suber L.; soil macrofauna

Analysis of spatial patterns of oak decline in cork oak woodlands in Mediterranean conditions - Costa, Augusta; Pereira, Helena; Madeira, Manuel (Annals of Forest Science, 2010)
• Cork oak mortality is a recurrent problem in southwestern Portugal. Despite the perception of increasingly visible damage in oak woodlands on drought-prone sites, the role of the various environmental factors in their decline is not clear. • To describe the spatial patterns of cork oak (Quercus suber L.) mortality, a cork oak mortality index (MI) was determined for each landscape feature (agroforestry system, soil type, slope and aspect) using a GIS approach. To achieve this goal, a logistic regression model was formulated analyzing interactions between landscape attributes and allowing a prediction of cork oak mortality. • Maximum values of MI were found in (i) shrublands and open woodlands with shrub encroachment (MI 6 and 3, respectively), where competition for soil water between tree and understory increases; and (ii) on lower slopes in the rounded hilltops and smooth hillsides or shallow soils where access to groundwater resources during summer drought is diﬃcult. • The model highlighted the importance of the agroforestry systems on cork oak mortality and may be used to identify sensitive areas where mitigation actions should be employed in a scenario of increasing drought severity in these Mediterranean ecosystems.
Keywords: Logistic regression; Oak decline; oak mortality; Quercus suber L.; Remote sensing

Characterization of Sardinian cork oak (Quercus suber L.) genetic resources for economically important traits - Bullitta, Simonetta; Dettori, Sandro; Manchinu, Manuela; Filigheddu, Maria Rosaria; Piluzza, Giovanna (Genetic Resources and Crop Evolution, 2010)
Considering the very high socio economic value of cork oak (Quercus suber L.) in Mediterranean areas, a better knowledge of local genetic resources is necessary in order to reach a good balance between the conservation issues and the need of an efﬁcient cork production network. In such frame, local germplasm of Q. suber from the main cork production areas of Sardinia was analysed for DNA and isozyme polymorphisms and for cork quality in relation to some environmental parameters. A total number of 24 sample stands of cork oak were selected, representing typical vegetation, sylvicultural and cork quality features within the eight identiﬁed cork growing areas in Sardinia. Considerable variation was found between cork oak stands of the different areas. Results of the principal component analysis performed on the cork quality data and environmental characters of the eight areas, showed that the ﬁrst three components explain 72.2% of the variation. The major characters involved in this differentiation were cork quality characters such as dimensional recover, moisture and Mg content of the cork and also elevation of stands m a.s.l. for the ﬁrst component. The second component appears to be determined by some climatic parameters (average annual temperature and average of the minimum temperatures of coldest month) and by the Fe and Zn in the cork. For the third component, major characters involved in differentiation are average annual rainfall, bark thickness and Ca content in the cork.
Keywords: cluster analysis; Cork quality; DNA polymorphisms; Principal component analysis; Quercus suber L.

Análise Espacial da Mortalidade do Sobreiro em S. Bartolomeu da Serra (Santiago do Cacém) - Costa, Augusta; Pereira, Helena; Madeira, Manuel (Congresso Florestal Nacional, 6º, Ponta Delgada, 2009 - A floresta num mundo globalizado, 2009)
Avaliou-se a distribuição espacial da mortalidade do sobreiro (Quercus suber L.) na área da freguesia de S. Bartolomeu da Serra (Santiago do Cacém), integrada numa região em que ela ocorre com elevada incidência, através de técnicas de detecção remota (SIG), e determinou-se a probabilidade de ocorrência de mortalidade através da aplicação de um modelo de regressão logística. Determinou-se um índice de mortalidade e identificaram-se as unidades fisiográficas com maior probabilidade de mortalidade em três sistemas agroflorestais distintos: floresta de sobreiro (florestas densas), montado de sobro tradicional (florestas abertas em sistemas dominantemente agrícolas, com culturas arvenses sob coberto) e incultos (florestas abertas em sistemas dominantemente incultos, com matos sob coberto). A mortalidade do sobreiro é significativamente diferente para os três tipos de sistemas agro-florestais. A mortalidade é influenciada por características físicas da paisagem como o solo, o declive e a exposição. Em solos pouco profundos ou em solos mais compactos, a mortalidade é mais frequente, mostrando a importância do desenvolvimento radicular em profundidade do sobreiro em regiões susceptíveis a extensos períodos de secura.
The following values have no corresponding Zotero field: periodical: Congresso Florestal Nacional, 6º, Ponta Delgada, 2009 - A floresta num mundo globalizado
Keywords: declínio do montado de sobro; detecção remota; mortalidade do sobreiro; Quercus suber L.; regressão logística

Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor (Journal of Agricultural and Food Chemistry, 2009)
Phenolic compounds, namely, hydrolyzable tannins and low molecular weight phenolic compounds, were isolated and purified from Portuguese cork from Quercus suber L. Some of these compounds were studied to evaluate their antioxidant activity, including free-radical scavenging capacity (DPPH method) and reducing capacity (FRAP method). All compounds tested showed significant antioxidant activity, namely, antiradical and reducing properties. The antiradical capacity seemed to increase with the presence of galloyl groups. Regarding the reducing capacity, this structure-activity relationship was not so clear. These compounds were also studied to evaluate the growth inhibitory effect on the estrogen responsive human breast cancer cell line (ERþ) MCF-7 and two other colon cancer cell lines (Caco-2 and HT-29). Generally, all the compounds tested exhibited, after a continuous exposure during a 48 h period, a dose-dependent growth inhibitory effect. Relative inhibitory activity was primarily related to the number of phenolic hydroxyl groups (galloyl and HHDP moieties) found in the active structures, with more groups generally conferring increased effects, except for HHDP-di-galloyl-glucose. Mongolicain B showed a greater potential to inhibit the growth of the three cell lines tested, identical to the effect observed with castalagin. Since these compounds are structurally related with each other, this activity might be based within the C-glycosidic ellagitannin moiety.
From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)From Duplicate 2 (Antioxidant and Biological Properties of Bioactive Phenolic Compounds from Quercus suber L. - Fernandes, Ana; Fernandes, Iva; Cruz, Luís; Mateus, Nuno; Cabral, Miguel; de Freitas, Victor)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 19888728
Keywords: antioxidants; Antioxidants: chemistry; Antioxidants: isolation & purification; Antioxidants: pharmacology; Antitumor activity; Cell Line; Cell Proliferation; Cell Proliferation: drug effects; Cork; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: chemistry; Hydrolyzable Tannins: isolation & purification; Hydrolyzable Tannins: pharmacology; phenolic compounds; Plant Extracts; Plant Extracts: chemistry; Plant Extracts: isolation & purification; Plant Extracts: pharmacology; Quercus; Quercus suber L.; Quercus: chemistry; Tumor

An approach to cork oak forest management planning: a case study in southwestern Portugal - Costa, A.; Oliveira, A. C.; Vidas, F.; Borges, J. G. (European Journal of Forest Research, 2009)
This paper presents results of research aiming at the development of tools that may enhance cork oak (Quercus suber L.) forest management planning. Speciﬁ- cally, it proposes an hierarchical approach that encompasses the spatial classiﬁcation of a cork oak forest and the temporal scheduling of cork harvests. The use of both geographical information systems and operations research techniques is addressed. Emphasis is on the achievement of cork even ﬂow objectives. Results from an application to a case study in the Charneca Plioce´nica of Ribatejo in southern Portugal encompassing a cork oak forest extending over 4.8 thousand ha are discussed. They suggest that the proposed approach is capable of effective spatial classiﬁcation of cork oak management units. They further suggest that it may be used to select optimal cork even ﬂow scheduling strategies. Results also show that the proposed approach may lead to a substantial increase in net present value when compared to traditional approaches to cork oak forest management planning.
Keywords: cork harvesting; Cork oak forest management; Harvest scheduling; Linear programming; Quercus suber L.

Identification of new molecules extracted from Quercus suber L. cork. - Coquet, Corinne; Ferré, Elisée; Peyronel, Dominique; Dal Farra, Claude; Farnet, Anne Marie (Comptes rendus biologies, 2008)
Various methods of suberin extraction have been used in order to identify monomers of this complex polymer. Pre-extraction of waxes has allowed us to identify for the first time 3-friedelanol as a terpen from cork. Moreover, the wax chemical composition found here varied from previous results since cerin was not identified while friedelin and betulin were. Three fractions were obtained: a polymeric, a monomeric and a low molecular weight fraction, the last of which has never before been described. 2,6-heptanediol was found to be the main compound of this fraction. Furthermore, depolymerisation at room temperature gives the same yields as those obtained at reflux, defining an easier and cheaper methodology.
The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 18940700
Keywords: 2.6-heptanediol; 3-friedelanol; Quercus suber L.; suberin; Terpens

Responses of Photosynthetic and Defence Systems to High Temperature Stress in Quercus suber L Seedlings Grown under Elevated CO2 - FARIA, T.; Vaz, M.; Schwanz, P.; PolIe, A. (Plant biology (Stuttgart, Germany), 2008)
Growth in elevated CO2 led to an increase in biomass production per plant as a result of enhanced carbon uptake and lower rates of respiration, compared to ambient C02-grown plants. No down-regulation of photosynthesis was found after six months of growth under elevated CO2. Photosynthetic rates at 15°C or 35°C were also higher in elevated than in ambient C02-grown plants, when measured at their respective CO2 growth condition. Stomata of elevated C02-grown plants were less responsive to temperature as compared to ambient CO2 plants. The after effect of a heat-shock treatment (4 h at 45°C in a chamber with 80% of relative humidity and 800—1000 tmol rn2 photon flux density) on Amax was less in elevated than in ambient C02-grown plants. At the photochemical level, the negative effect of the heat-shock treatment was slightly more pronounced in ambient than in elevated CO2-grown plants. A greater tolerance to oxidative stress caused by high temperatures in elevated C02-grown plants, in comparison to ambient CO2 plants, is suggested by the increase in superoxide dismutase activity, after 1 h at 45°C, as well as its relatively high activity after 2 and 4 h of the heat shock in the elevated C02-grown plants in contrast with the decrease to residual levels of superoxide dismutase activity in ambient C02-grown plants immediately after 1 h at 45°C. The observed increase in catalase after 1 h at 45°C in both ambient and elevated C02-grown plants, can be ascribed to the higher rates of photorespiration and respiration under this high temperature.
Keywords: catalase; Elevated CO2; photosynthesis; Quercus suber L.; superoxide dismutase; Temperature

Diplofuranones A and B , two further new 4-monosubstituted 2 ( 3H ) -dihydrofuranones produced by Diplodia corticola , a fungus pathogen of cork oak - Evidente, Antonio; Andolfi, Anna; Fiore, Michele; Spanu, Emanuela (ARKIVOC, 2007)
Two new 4-monosubstituted 2(3H)-dihydrofuranones, named diplofuranones A and B, were isolated from liquid cultures of Diplodia corticola, a plant pathogenic fungus causing a canker disease of cork oak (Quercus suber L.). The same fungus also produces several metabolites such as the diplopyrone, the (3S,4R)-trans- and the (3R,4R)-cis-4-hydroxymellein, the sapinofuranone B and its (S,S)-enantiomer, the well known sphaeropsidins A-C, and the diplobifuranylones A and B. The diplofuranones A and B were characterised, using spectroscopic (essentially NMR and MS techniques) methods, as the 4-[(1E,3E)-5-hydroxyhexadienyl]butan-4-olide and its corresponding 3,4-dihydro side chain derivative. The stereochemistry of the stereogenic secondary hydroxylated carbon of the side chain of diplofuranone A was determined by application of Mosher’s method and proved to be R. Diplofuranone A tested at 0.2 mg mL-1 on non-host plant did not show phytotoxic activity.
Keywords: canker disease; Cork oak; Diplodia corticola; phytotoxic metabolites; Quercus suber L.

Evaluation of the energy value of plant species consumed by the Barbary Deer (Cervus elaphus barbarus, Bennet 1833) in the area of El Ayoune (El Kala National Park, Algeria) - Arbouche, Halima Saadia; Arbouche, Fodil (REVUE D ECOLOGIE-LA TERRE ET LA VIE, 2007)
Plant species taken for food by the Barbary Deer were determined by direct observation during one year. On the basis of their chemical composition and phenological stage, the energy value of the grazed plant species has been expressed in stag-units as suggested by Brelurut et al. (1990). Results show that the more energy-giving elements are plants from the herbaceous layer and the acorns of Cork Oak (Quercus suber). From the shrubby layer, the Strawberry-tree (Arbustus unedo) comes first with an energy value comparable to that of green grass fodder, followed by Tree Heath (Erica arborea), Lentisc (Pistacia lentiscus) and Filaria (Phillyrea augustifolia) with energy values comparable to those of grass hays. The energy values of the other shrubby plant species are comparable with those of cereal straws; they do not ensure but the needs for maintenance.
Key W: ASKey W: ASThe following values have no corresponding Zotero field: pub-location: 57 RUE CUVIER, 75005 PARIS 5, FRANCE publisher: SOC NATL PROTECTION NATURE ACCLIMATATION FRANCE
Keywords: grazed plant species; herbaceous; Quercus ilex.L; Quercus suber L.

Fragmentation of Suberin and Composition of Aliphatic Monomers Released by Methanolysis of Cork from Quercus suber L.,Analysed by GC-MS, SEC and MALDI-MS - Bento, M. F.; Pereira, H.; Cunha, M. Á; Moutinho, A. M. C.; van den Berg, K. J.; Boon, J. J.; van den Brink, O.; Heeren, R. M. A. (Holzforschung, 2005)
Suberin from extractive-free cork from Quercus suber L. was depolymerised by methanolysis using different sodium methanolate (NaOMe) concentrations. 1% and 3% NaOMe completely removed suberin from cork (54%–56% of extractive-free cork), but for lower concentrations there was incomplete solubilisation; with 0.05% NaOMe, only approximately 80% of total suberin was removed. The monomeric composition of the extracts differed significantly: for the 0.05% NaOMe, only alkanoic acids and diacids were found; the yield of v-hydroxy acids increased with reactant concentration, as well as alkanols and ferulic acid. Results from light scattering, SEC and MALDI-MS showed that soluble oligomeric fragments containing suberinic acids were present in the methanolysis mixture. The molecular weight of these oligomeric fragments decreased with higher sodium methanolate concentrations.
Keywords: Cork; MALDI-MS; Methanolysis; Quercus suber L.; SEC; Suberin fragmentation

Quercus suber cork extract displays a tensor and smoothing effect on human skin: an in vivo study. - Coquet, C.; Bauza, E.; Oberto, G.; Berghi, A.; Farnet, A. M.; Ferré, E.; Peyronel, D.; Dal Farra, C.; Domloge, N. (Drugs under experimental and clinical research, 2005)
Recently, it has become indispensable for anti-aging active ingredients to provide a visible and immediate smoothing antiwrinkle effect. In Quercus suber, suberin is the most important structural component of cork cell walls. Studies have shown that suberin is made up mostly of hydroxycarboxylic acids and that it is endowed with many special mechanical and chemical properties that evoke a possible smoothing effect on the surface of the skin. Therefore, we were interested in investigating the effect of this cork extract on the skin's surface in a double-blind clinical study. The study was conducted in 15 healthy volunteers, aged 22 to 52 years. The volunteers applied a gel formula with 3% of cork extract, or placebo gel, on each forearm. Skin surface roughness was evaluated visually by pictures and by silicone replicas 1 and 2 h after application, followed by statistical analysis using the matched-pairs McNemar statistical test. McNemar analysis of the pictures revealed that application of cork extract on the skin resulted in a highly significant reduction of roughness 1 h after application. This effect was observed in 73.3% of volunteers. Two hours after cork extract application, a highly significant improvement of skin roughness was found in 78.6% of volunteers. Moreover, silicone replica treatment confirmed significant improvement in average of roughness at 2 h. These results demonstrate that cork extract provides a remarkable and highly significant tensor and smoothing effect on the skin, which could be of great use in anti-aging skin care products.
Journal Article,Randomized Controlled Trial,Journal Article,Randomized Controlled Trial,The following values have no corresponding Zotero field: pub-location: Vincience Research Center, Sophia Antipolis, France.
Keywords: 2; 3-friedelanol; 6-heptanediol; Quercus suber L.; suberin; Terpens

Micropropagation of cork oak (Quercus suber L.) by axillary buds - El Kbiach, M. L.; Lamarti, A.; Abdali, A.; Badoc, A. (ACTA BOTANICA GALLICA, 2004)
The in vitro regeneration from cork oak axillary buds was investigated. Different macronutrient formulas supplemented with MS micronutrients, vitamins and 3% sucrose were tested on shoot multiplication and rooting phases. The WPM macronutrients improved caulogenesis and shoot multiplication. Rooting was achieved on WPM 1/2 macronutrients. Dipping the base of the shoots in an IBA concentrated solution improved the rooting phase. 92% of the rooted plants were successfully potted on horticultural substrate with a high relative humidity.
The following values have no corresponding Zotero field: pub-location: FACULTE DE PHARMACIE, BP 83, F-59006 LILLE-CEDEX, FRANCE publisher: SOC BOTANIQUE FRANCE
Keywords: browning; contaminants; Cork oak; micropropagation; phenolic compounds; Quercus suber L.; tissue culture

USE OF THERMAL IMAGING TECHNIQUES AND XANTHOPHYLLS CONTENT FOR DETERMINATION OF STRESS IN CORK OAK (QUERCUS SUBER L.) - Tronina, L.; Grant, O. M.; Ramalho, J. C.; Chaves, M. M. (ACTA PHYSIOLOGIAE PLANTARUM, 2004)
Understanding the responses of cork oak (Quercus suber L.) to actual and predicted summer conditions is essential to determine the future sustainability of cork oak woodlands in Iberia. Thermal imaging may provide a rapid method for monitoring the extent of stress. The ecophysiology of cork trees was studied over three years. Three treatments were applied by means of rainfall capture and irrigation, with plots receiving 120%, 100%, or 80% of natural precipitation. Despite stomatal closure, detected using both thermal imaging and porometry, leaf water potential fell during the summer, most drastically during the third year of accumulative stress. The quantum efficiency (ΦPSII) and the maximum efficiency Formula of photosystem II also fell more intensely over the third summer, while non-photochemical quenching (NPQ) increased. The reduced precipitation treatment sporadically further reduced leaf water potential, stomatal conductance (gs), IG (an index of gs derived from thermal imaging), ΦPSII, and Formula, and increased leaf temperature and NPQ. It is concluded that these are very resilient trees since they were only severely affected in the third year of severe drought (the third year registering 45% less rainfall than average), and removing 20% of rainfall had a limited impact.
Key words: ASKey words: ASThe following values have no corresponding Zotero field: pub-location: TIERGARTENSTRASSE 17, D-69121 HEIDELBERG, GERMANY publisher: SPRINGER HEIDELBERG
Keywords: Quercus suber L.; Stress; thermal imaging

Microspore-derived embryos from Quercus suber anthers mimic zygotic embryos and maintain haploidy in long-term anther culture. - Bueno, María a; Gomez, Arancha; Sepulveda, Federico; Seguí, José M.; Testillano, Pilar S.; Manzanera, Jose a; Risueño, Maria-Carmen (Journal of plant physiology, 2003)
Microspore-derived embryos produced from cork oak anther cultures after long-term incubations (up to 10-12 months) were analysed in order to determine the genetic variability and ploidy level stability, as well as morphology, developmental pattern and cellular organisation. Most of the embryos from long-term anther cultures were haploid (90.7%), corresponding to their microspore origin. The presence of a low percentage of diploid embryos (7.4%) was observed. Microsatellite analysis of haploid embryos, indicated different microspores origins of the same anther. In the diploid embryos, homozygosity for different alleles was detected from anther wall tissues, excluding the possibility of clonal origin. The maintenance of a high proportion of haploid embryos, in long-term anther cultures, is similar in percentage to that reported in embryos originating after 20 days of plating (Bueno et al. 1997). This suggests that no significant alterations in the ploidy level occurred during long incubations (up to 12 months). These results suggest that ploidy changes are rare in this in vitro system, and do not significantly increase during long-term cultures. Microscopical studies of the microspore embryos in various stages revealed a healthy and well developed anatomy with no aberrant or chimeric structures. The general morphology of embryos appearing at different times after plating, looked similar to that of earlier embryos, as well as the zygotic embryos, indicating that they represent high quality material for cork oak breeding.
The following values have no corresponding Zotero field: accession-num: 12964871
Keywords: Cytochemistry; DNA-Analysis; flow cytometry; haploid embryos; immunocyto- chemistry; Quercus suber L.

Propagação Vegetativa de Sobreiros Seleccionados - de Freitas, Maria Isabel Carrasquinho (Silva Lusitana, 2002)
The aim of this investigation was to evaluate the possibilities of vegetative propagation techniques of adult cork oak trees so as to develop an approach applicable to a genetic improvement breeding program. Bud grafting and cuttings were used to multiply and mass propagate selected cork oak trees. Forty-six cork oak trees were reproduced from clone banks. September proved to be a better season for grafting than June/July. Rooting season and the temperature of the rooting substrate were demonstrated to be important factors in juvenile cuttings response. The highest rooting ability was achieved in August with a rooting substrate temperature of 28°C (57.0%). The best rooting rate was obtained by maintaining cuttings in rooting media for four months. The application of IBA influenced rooting ability both in cuttings from seedlings and those from the clone bank. Nevertheless, juvenile material needed a lower IBA concentration (0.5%) than the older material (1%). The clone and age of grafting were shown to influence the rooting ability. The decrease of rooting ability with age of grafting requires a dynamic management of the clone bank. The vegetative propagation of selected adult cork oak trees seems to be a viable technique, establishing a prior clone bank, by means of grafting, and then mass propagation through cuttings of this material.
The following values have no corresponding Zotero field: publisher: scielopt
Keywords: Bud grafting; Clones; Cuttings; Quercus suber L.; vegetative propagation

A dendroclimatological approach to diameter growth in adult cork-oak trees under production - Costa, A.; Pereira, H.; Oliveira, A. (Trees, 2001)
The diameter growth of mature cork oaks under cork production in southwestern Portugal was studied during a 9-year cork-production cycle in relation to fluctuations in precipitation and temperature, and to drought indices combining the two variables. A dendroclimatological approach was applied to the series of 8 complete years contained in the cork-production cycle and growth effects were removed by standardization and calculation of annual growth indices. The most important factor positively influencing diameter growth was cumulative precipitation in the growing season (January–June) and in the previous autumn and winter (October/November of the previous year–June). The monthly temperature is a less influential factor, negatively correlated with diameter growth in high summer drought (August) and positively correlated at the beginning of physiological activity (March).
Keywords: climatic fluctuations; dendroclimatology; diameter growth; Mediterranean climate; Quercus suber L.

Estudio de la influencia de la fertilizacion nitrogenada y la iluminacion sobre atributos morfologicos y fisiologicos de brinzales de Q.suber L. CULTIVADO EN VIVERO. RESULTADOS DEL 1er. AÑO EN CAMPO - Martínez Romero, G.; Planelles González, R.; Zazo Muncharaz, J.; Bela Quero, D.; Vivar Sanz, A.; López Arias, M. (III Congreso Forestal Español Congreso, 2001)
This essay studies the influence of fertilization and illumination of Q.suber L. in container seedlings. Plants were tested in three diferents levels of fertilization (control substrate, fertilizated substrate and fertilizated substrate plus nitrogen supplied) with two of illumination (full light conditions and a reduction of 50% illumination). After the first year in nursery, plants was installed in survey parcels, where growing measures and survival rates were studied
The following values have no corresponding Zotero field: periodical: III Congreso Forestal Español Congreso pub-location: Granada
Keywords: Cork oak; fertilization; ilumination; Quercus suber L.

Cork suberin as an additive in offset lithographic printing inks - Cordeiro, N.; Blayo, A.; Belgacem, N. M.; Gandini, A.; Pascoal Neto, C.; LeNest, J.-F. (Industrial Crops and Products, 2000)
Suberin oligomers, isolated from cork (Quercus suber L.), were used as additives in ‘Waterless’ and vegetable-oil ink formulations, in the range of 2–10% w:w. The rheological behaviour of the suberin oligomers as well as of the inks, with and without suberin, were investigated as a function of temperature. It was shown that the addition of suberin induces a decrease of viscosity of both inks. The tack of pristine inks, suberin oligomers and their mixtures were determined at different temperatures: the variation of this parameter as a function of time provided information about the drying kinetics of these formulations. The tack of the ‘Waterless’ ink was found to increase with the introduction of suberin, whereas that of vegetable-oil based counterparts decreased. All the trends observed were interpreted in terms of the differences in composition between the two types of inks. Preliminary printing tests were carried out with the various suberin-containing inks
Keywords: Additive; Quercus suber L.; rheological properties; suberin; Tack; Vegetable oil-based ink; Viscosity; Waterless ink

Observations sur la dynamique du développement du Diplodia mutila Fr. apud Mont. sur le chêne-liège, Quercus suber L., au Maroc - El-Badri, Naïma; Abadie, Michel (Cryptogamie Mycologie, 2000)
Mamora forest in Rabat (Morocco) was a wide forest of cork oak which is rapidly disappearing. This crisis is caused by both human exploitation and overgrazing by animals. This situation is also affected by the existence of harmful insects and parasitic fungi. One of the most common species is Diplodia mutila Fr. apud Mont. (group of Coelomycetes) anamorph of Botryosphaeria stevensii Shoem., which causes withering and cankers on trunks and branches. The electron microscope observations on pycnosporogenesis and the study of the relation plant-host-pathogen show the structure and the biological cycle of Diplodia mutila, the endophytic and the systemic development of the pathogen and the irreversible damage on the plant host. This study is a contribution to the research on cork-oak forest protection.
Keywords: decline; Diplodia mutila Fr. apud Mont.; FOREST; Mamora; Morocco; pathology; Quercus suber L.; ultrastructure

Spectral editing of 13C cp/MAS NMR spectra of complex systems: application to the structural characterisation of cork cell walls. - Lopes, M. H.; Sarychev, A.; Neto, C. P.; Gil, a M. (Solid state nuclear magnetic resonance, 2000)
A mathematical method of obtaining 13C CP/MAS subspectra of single components of a complex system is presented and applied to three- and four-component systems. The method is based on previously reported work that exploits different proton relaxation properties for different domains of an heterogeneous system. However, unlike the original method that obtained subspectra through a trial-and-error approach, the method here presented solves the problem mathematically, thus avoiding the time-consuming and non-rigorous trial-and-error step. The method is applied to mixtures of three and four polymers and to a more complex system: cork cell walls. As expected, as the number of components increases, the sharing of relaxation properties between different components is increasingly probable, either due to incidental coincidence of relaxation times or to specific interactions and intimate mixing of compounds. While this hinders the calculation of the subspectra of single chemical components, it may provide useful information about inter-component interactions. This possibility was demonstrated by the application of this method to cork cell walls. Both three-component and four-component approaches showed that three domains exist in cork cell walls: carbohydrate/lignin matrix, mobile suberin close to (probably bonded to) lignin groups (about 42% w/w) and hindered suberin close to (probably bonded to) carbohydrate-OCH2O groups (about 4% w/w).
The following values have no corresponding Zotero field: accession-num: 10868562
Keywords: 13CCPrMAS NMR; Cork; Polymer; Quercus suber L.; Relaxation; Spectral editing

Urethanes and polyurethanes from suberin 2: synthesis and characterization - Cordeiro, N.; Belgacem, M. N.; Gandini, A.; Neto, C. P. (INDUSTRIAL CROPS AND PRODUCTS, 1999)
Polyurethanes based on suberin from cork of Quercus suber L. and conventional isocyanate monomers were prepared and fully characterized in terms of both structure (FTIR and H-1 NMR spectroscopy) and thermal properties (differential scanning calorimetry and thermogravimetric analysis). Two fractions were systematically isolated, namely (i) methylene-chloride soluble products, which corresponded to linear and branched macromolecules and (ii) methylene-chloride insoluble products, representing the crosslinked material. The structures of these polymers were regular and no appreciable side reactions were detected. DSC analyses provided information about the glass transition temperature of both fractions and this parameter was correlated with the stiffness of the isocyanate used. The TGA of these polyurethanes showed that they started to degrade at about 175 degrees C and that the residue at 400 degrees C was around 50%. The highest amounts of insoluble fractions, as well as the highest T-g,s, were reached when an initial \{[\}NCO]/\{[\}OH] of unity was used. (C) 1999 Elsevier Science B.V. All rights reserved.
The following values have no corresponding Zotero field: pub-location: PO BOX 211, 1000 AE AMSTERDAM, NETHERLANDS publisher: ELSEVIER SCIENCE BV
Keywords: Cork; glass transition; polyurethanes; Quercus suber L.; suberin; thermal properties

Cork suberin as a new source of chemicals. 1. Isolation and chemical characterization of its composition. - Cordeiro, N.; Belgacem, M. N.; Silvestre, a J.; Pascoal Neto, C.; Gandini, A. (International journal of biological macromolecules, 1998)
Extractive-free cork from Quercus suber L. was submitted to a solvolysis treatment with methanolic NaOH which yielded 37% (o.d. cork) of suberin. This mixture of compounds was thoroughly characterized by FTIR, 1H- and 13C-NMR, gas chromatography coupled with mass spectrometric (GC-MS) analysis, vapour pressure osmometry (VPO), mass spectrography (MS) and gel permeation chromatography (GPC). After derivatization, the main components of the volatile fraction, representing less than half of the total, were found to be omega-hydroxymonocarboxylates, alpha, omega-dicarboxylates, simple alkanoates and 1-alkanols, all with chain lengths ranging from C16 to C24. A second fraction, with an average molecular weight about three times higher, was detected by VPO, MS and GPC. The presence of this important fraction in cork suberin had not been recognized in earlier studies. Both fractions constitute interesting precursors for the elaboration of new materials.
The following values have no corresponding Zotero field: accession-num: 9585884
Keywords: Alkaline methanolysis; Chemical characterization; Cork; Molecular weight distribution; Quercus suber L.; suberin

Identification of the main fatty acids component of the cork suberine by GC/MS - Bleton, J.; Mejanelle, P.; Goursaud, S.; Tchapla, A. (ANALUSIS, 1998)
The aim of this work was to verify the presence of cork (Quercus Suber) in two samples of linoleum the beginning of the twentieth century Using GC/MS after acidic methanolysis and silylation, it was possible to identify most of the components of a modern sample of cork. The dominant is a lipid polymer: the suberin. Its monomeric composition is examined in details.
APSAPSThe following values have no corresponding Zotero field: pub-location: 7, AVE DU HOGGAR, PARC D ACTIVITES COURTABOEUF, BP 112, F-91944 LES ULIS CEDEXA, FRANCE publisher: E D P SCIENCES
Keywords: Cork; GC/MS; Quercus suber L.; suberin

A quantitative approach to cork oak forest management - Borges, JoséG; Oliveira, Ângelo C.; Costa, Maria a (Forest Ecology and Management, 1997)
Mathematical programming is one quantitative technique that can be used for strategic and tactical natural resources planning. It has been extensively used both at private and public forest planning levels. Nevertheless, most applications concentrate on modelling of systems involving timber harvesting. This paper focuses on cork oak (Quercus suber L.) forest management. It summarizes the methodology to follow in order to generate information needed for modelling purposes. It formulates a cork oak forest management problem using a linear programming model. A case study is used to illustrate the procedure used. The results of the research on a modelling approach to cork oak forest management for an area extending over 5272 ha in the Portuguese submediterranean ecological region are presented. Extensions to this study are identified.
Keywords: Forest regulation; Harvest scheduling; Linear programming; Mediterranean forestry; Quercus suber L.; Strategic planning

Annual cork-ring width variability of Quercus suber L. in relation to temperature and precipitation (Extremadura, southwestern Spain) - Caritat, A.; Molinas, M.; GUTIÉRREZ, E. (Forest Ecology and Management, 1996)
A 14 year sequence of cork-ring width chronology is correlated with rainfall and temperature data. Cork specimens were obtained from three cork peel samplings carried out in 1989, 1991 and 1993 from a cork ‘dehesa’ in Ckeres, Spain. Average width of cork-rings varied between 2.05 and 4.37 mm. The cork-ring width chronologies of the three peel-off samplings show definite agreement patterns. Differences in ring width in years of greater and lesser growth are clearly marked. Correlation between ring width and rainfall indicates that the rain periods with the greatest influence on cork growth are those occurring from November to June, followed by those from November to September. Temperature, on the other hand, shows a negative correlation with cork growth, except during the coldest months and the months of April and September when temperature possibly has a crucial influence on phellogen activation.
Keywords: climatic fluctuations; cork growth; cork-oak; cork-ring chronology; Quercus suber L.

Growth at elevated CO2 leads to down-regulation of photosynthesis and altered response to high temperature in Quercus suber L. seedlings - FARIA, T.; Wilkins, D.; Besford, R. T.; Vaz, M.; Pereira, J. S.; Chaves, M. M. (Journal of Experimental Botany, 1996)
The effects of growth at elevated CO2 on the response to high temperatures in terms of carbon assimilation (net photosynthesis, stomatal conductance, amount and activity of Rubisco, and concentrations of total soluble sugars and starch) and of photochemistry (for example, the efficiency of excitation energy captured by open photosystem II reaction centres) were studied in cork oak (Quercus suber L.). Plants grown in elevated CO2 (700 ppm) showed a down-regulation of photosynthesis and had lower amounts and activity of Rubisco than plants grown at ambient CO2 (350 ppm), after 14 months in the greenhouse. At that time plants were subjected to a heat-shock treatment (4 h at 45°C in a chamber with 80% relative humidity and 800–1000 µmol m−2 s−1 photon flux density). Growth in a CO2-enriched atmosphere seems to protect cork oak leaves from the short-term effects of high temperature. Elevated CO2 plants had positive net carbon uptake rates during the heat shock treatment whereas plants grown at ambient CO2 showed negative rates. Moreover, recovery was faster in high CO2-grown plants which, after 30 min at 25°C, exhibited higher net carbon uptake rates and lower decreases in photosynthetic capacity (Amax as well as in the efficiency of excitation energy captured by open photosystem II reaction centres (FvJFm than plants grown at ambient CO2. The stomata of elevated CO2 plants were also less responsive when exposed to high temperature.
10.1093/jxb/47.11.175510.1093/jxb/47.11.1755
Keywords: acclimation; Elevated CO2; photo- synthesis; Quercus suber L.; Temperature

Crecimiento radial del corcho de reproducción de los alcornocales catalanes y valencianos - Fos, S.; Barreno, E. (Scientia gerundensis, 1994)
Eastern cork-oak forests are present in territories with different environmental characteristics, allowing to raise comparative studies between them. This work is an attempt to evaluate the radial growt differences of the reproduction cork, using tschniques of optical microscopy, having developed a new methodology. Thus, severa1 sites from catalonian and valencian cork-oak forests have been selected. In the quantification of this growth, the contribution of each cork type (early cork and late cork) in the annual growing rings have been differentia- ted. The annual increments measwed in catalonian corks have an average of 2.958 mm, being a bit lower in Castell6n with 1.622 mm. These differences in the annual growing rings are due to the early development higher in catalonian cork (2.623 mm) than in valencian ones (1.235 mm), late cork thickness is similar in the two areas. These differences seem to be related with the escarce summer dry period in catalonian cork-oak forests. Important anato- mical differences related with the mentioned ombroclimatic asimetries have been observed too.
Keywords: Anatomy; bioclimatology; cork-oak; Quercus suber L.; Radial growth

El crecimiento radial del alcornoque en cinco parcelas de alcornocal de Girona - Caritat, A.; Molinas, M.; Oliva, M. (Scientia gerundensis, 1992)
Tree rings of Quercus suber L. are porous and difficult to read because of the irregular growth rhythm. Radial growth has been measured in five experimental plots situated in the region of Girona (Catalonia, NE Spain). Cores of ten standard trees of each plot were extracted using a Pressler borer. In three plots woody disks from standard trees were also obtained. Tree rings were examinated under binocularlens. The CATRAS computer program (Anio1,1983 ) was used to find statistical parameters. Tree rings have an average width changing from 1,21 to 3,74 mm, while average standard deviation varies from 0,24 to 1,88 mm. and autocorrelation from 0,008 to 0.894 . These values are similar to those found in other Mediterranean Quercus, like Q. ilex L. The studied cork-oak plots ,with diametrical classes between 5 and 57 cm, show regular growth characteristic of young forest. The St. Hilari plot has the maturest trees, (diametrical classes from 24 to 57 cm) and this fact was reflectedin thegrowthcurve. Suddengrowthincreases are attributed to forestry management measures like clearing or selective cutting down. The effects of periodic cork extractions could no be clearly appreciated in this study.
Keywords: cork-oak; Mediterranean sclerophylls; Quercus suber L.; Radial growth; wood rings